Design, synthesis, and target identification of new hypoxia-inducible factor 1 (HIF-1) inhibitors containing 1-alkyl-1H-pyrazole-3-carboxamide moiety. (15th September 2021) - Sakai, Marina; Takahashi, Nobuaki; Ikeda, Hiroaki; Furutani, Yutaka; Higuchi, Shoko; Suzuki, Takehiro; Dohmae, Naoshi; Kobayashi, Sayaka; Harada, Hiroshi; Kojima, Soichi; Matsuura, Tomokazu; Hattori, Akira; et al.
Graphical abstract: Highlights: A promising HIF-1 inhibitor KUSC-5037 was developed during extensive SAR study. A fluorescent probe and a bifunctional probe of KUSC-5037 were synthesized and utilized. ATP5B, a β subunit of Fo F1 -ATP synthase, was identified as the target protein. Abstract: Hypoxia-inducible factor 1 (HIF-1) is a promising drug target for cancer chemotherapy. In our screening program aimed at identifying new HIF-1 inhibitors by using a hypoxia-responsive luciferase reporter gene assay, KUSC-5001 containing the 1-alkyl-1 H -pyrazole-3-carboxamide moiety was found as a potential hit molecule. During an extensive structure–activity relationship (SAR) study, we developed a more effective HIF-1 inhibitor KUSC-5037 (IC50  = 1.2 μM). Under hypoxic conditions, KUSC-5037 suppressed the HIF-1α (a regulatory subunit of HIF-1) mRNA, causing decreases in the gene expression of HIF-1 target genes such as carbonic anhydrase 9 ( CA9 ) and vascular endothelial growth factor ( VEGF ) genes. Furthermore, by applying our fluorescent and bifunctional probes, ATP5B, a catalytic β subunit of mitochondrial Fo F1 -ATP synthase, was identified as a target protein of KUSC-5037 . These results indicate that the derivatives of KUSC-5037 containing the 1-alkyl-1 H -pyrazole-3-carboxamide moiety are promising lead molecules for the inhibition of HIF-1 signaling via Fo F1 -ATP synthase suppression.